Identification of α-isopropylmalate synthase mutants capable of overproducing L-leucine in Corynebacterium glutamicum - Yan-Feng Guo; Yu Lu; Lei Song; Jinghua Liu; Yi-Lei Wang; Guo-Qing Meng (All Life)
The enzyme α-isopropylmalate synthase (α-IPMS) catalyzes the first step of L-leucine biosynthesis and is regulated via feedback inhibition by L-leucine. The gene of α-IPMS variant from strain ARTP-L04 was cloned and sequenced. Interestingly, amino acid mutations of Gly92Asp, Ile162Val, Arg494His and Gly526Asp occurred in the α-IPMS variant. The enzyme of α-IPMS variant was characterized, and exhibited higher resistance to feedback inhibition by L-leucine. In the presence of 20 mM L-leucine, the activity of the α-IPMS variant was still retained at over 50%. The α-IPMS variant almost removed feedback inhibition by L-leucine, while there was no significant difference in specific activities of the α-IPMS variant and wild-type α-IPMS. For the α-IPMS variant, the capacity to overproduce L-leucine was evaluated by recombinant Corynebacterium glutamicum strains. Interestingly, expression of the α-IPMS variant could significantly enhance L-leucine production, especially co-expressed with acetohydroxyacid synthase (accumulating 7.79 g/L L-leucine). Collectively, our findings provided valuable insights into further development in genetic engineering for L-leucine production.